Assessing Trends of Vehicle Ownership and Use Among Tertiary Students in Kwame Nkrumah University of Science and Technology Campus, Ghana - Ernest Gyamfi; Oscar Agyemang Opoku (Pusat Publikasi Nusantara, 2024)
The study aims to assess trends of car ownership and usage among tertiary students on campus, with an emphasis on Kwame Nkrumah University of Science and Technology (KNUST). The research design employed in this study was descriptive survey, aiming to gather information from a sample population through their responses to specific questions. Data analysis was conducted using descriptive statistics, summarizing the responses quantitatively through bar charts, pie charts, frequencies, percentages as well as means and tables, created using Microsoft Excel. The results revealed that, a majority (70 percent) of the cars being used by students on the KNUST campus are owned by Ghanaian students with foreign students making up the minority of this number. The major challenges faced by students who own or use vehicles on campus are a lack of filling stations on and around campus, lack of student parking lots, and excess traffic. From the findings, it can be concluded that, students' psychological make-up is a major determinant of vehicle ownership among students. Moreover, the findings further revealed that most of the students who have vehicles on the campus exhibit or develop mostly negative habits after vehicle ownership and this in the long run may have negative effects on academic performance which is the sole purpose of being on campus. The study provides insights into the environmental and health impacts of increased vehicle use on university campuses, offering valuable insights for policy decisions, future research, and campus management, thereby enhancing student mobility.